Photometric Redshifts in the Hawaii-Hubble Deep Field-North. Issue Volume 11:Issue S319(2015) (17th August 2016) - Yang, G.; Xue, Y. Q.; Luo, B.; Brandt, W. N.; Alexander, D. M.; Bauer, F. E.; Cui, W.; Kong, X.; Lehmer, B. D.; Wang, J.-X.; Wu, X.-B.; Yuan, F.; et al.
Abstract: We derive z phot for sources in the entire ( 0.4 deg 2 ) H-HDF-N field with the EAzY code, based on PSF-matched broad-band ( U band to IRAC 4.5 μm) photometry. Our catalog consists of a total of 131, 678 sources. We find σNMAD = 0.029 for non-X-ray sources. We also classify each object as a star or galaxy through SED fitting. Furthermore, we match our catalog with the 2 Ms CDF-N main X-ray catalog. For the 462 matched non-stellar X-ray sources, we improve their z phot quality (σNMAD = 0.035) by adding three additional AGN templates. We make our photometry and z phot catalog publicly available.